Zarządzanie przez szanse na przykładzie "Wagony Świdnica SA" - Guliński, Patryk; Studziński, Witold (Management through Opportunity on Example "Wagony Świdnica SA", 2008)
The analysis introduces a concept of management through opportunity. The article discusses the description of Polish railway sector over the years, the situation of "Wagony Świdnica SA", and the implementation of concept of management through opportunity on the example. The most important aim of the present thesis is to show a connection between the conception of management trough opportunity and innovation and knowledge in an organization and their mutual permeation and complemention to achieve advantage over the competition.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 84-96